APPLICATION OF SPECIAL IRONS, PRODUCED BY METHOD OF FROSTING, FOR FRICTIONS OF CLUTCHES - A. M. Bodyako; A. A. Bodyako; S. Ju. Ostaltsev; A. A. Suponev; V. G. Ermalenok (Литьë и металлургия)
This article show the possibility of using special high-duty cast irons, received by a «Freezing-uр» technology of continuous- iterative casting, for producing friction discs.